“We don’t need ergonomics anymore, we need psychology!” – The human analysis needed for human-robot collaboration - Fletcher, Sarah; Eimontaite, Iveta; Webb, Phil; Lohse, Niels (AHFE International, 2022)
Human labour has always been essential in manufacturing and, still, no machine or robot can replace innate human complex physical (dexterity) and cognitive (reasoning) skills. Understandably, industry has constantly sought new automation technologies and largely only concerned itself with physical health and safety issues to improve / maintain production processes, but these industrial engineering approaches have largely overshadowed our understanding of wider social and emotional issues that can also significantly impact on human-system performance and wellbeing. In the current climate, industrial automation is rapidly increasing and crucial to manufacturing competitiveness, and requires greater, closer human interaction. Consequently, people’s cognitive-affective abilities have never been more critical and there has never been a more important time to thoroughly understand them. Moreover, industrial engineers are themselves now more aware and interested in understanding how people can better perform tasks in collaboration with intelligent automation and robotics. This paper describes why industry is only now realising the need for psychology, how far research has advanced our knowledge, and how a major UK project is working to develop new human behaviour models to improve effectiveness in the design of human-robot interactions in modern production processes. As one recent anecdotal comment from a UK industrialist set out: “we don’t need ergonomics anymore – our industrial engineers can do that, we need psychology”!
Keywords: Human-robot collaboration; Human-robot interaction; Human-systems integration; Cognitive ergonomics; Industrial psychology; Industrial robots; Technology acceptance